Ética da alimentação: porque devemos, segundo Kant, escolher uma alimentação adequada e saudável - Soares, Sônia (2015)
This thesis proposes the adoption of a practical and philosophic approach to the discussion about what should be a healthy food, in view of the actual problems concerning this subject (from famine to obesity), which affect food and nutritional security and constitute target of many official policies. In order to handle this task, this work resorts to ethic, pedagogical and anthropological concepts inherent to Immanuel Kant’s philosophy, as valuable contributions to the practice of the professional nutritionist committed to the support and accomplishment of the human right to adequate nutrition (DHAA). Under this assumption, it intends to surpass the prevailing idea inside the social programs and policies favoring the utilitarian argument. It considers rather that a healthy food is also a duty of virtue, according to the Kantian duties to one-self. The liberation of transgenic seeds in Brazil comes up as an example of the violation of the right to food security and affects it negatively, resulting from the conflict between politics and moral faced by the Brazilian government. This paper concludes that DHAA realization requires not only a committed state, but also committed citizens and suggests that Kant’s philosophy should offer important contributions to supporting the practice of the professional nutritionist, awarding him the necessary information about this matter.